Morphological diversity and habitat suitability modeling of Oncosperma tigillarium in coastal Riau, Indonesia - DETI NOVELA; TATIK CHIKMAWATI; NINA RATNA DJUITA; FITMAWATI FITMAWATI (Society for Indonesian Biodiversity, 2025)
Abstract. Novela D, Chikmawati T, Djuita NR, Fitmawati. 2025. Morphological diversity and habitat suitability modeling of Oncosperma tigillarium in coastal Riau, Indonesia. Biodiversitas 26: 3952-3964. Land-use change and forest fires are major threats to the survival of Oncosperma tigillarium in the coastal areas of Riau, Indonesia. Scientific information on the species’ morphological diversity, distribution, and habitat suitability remains limited, despite its significant ecological and economic value to local communities. Therefore, comprehensive research is urgently needed to support its conservation and sustainable use. This study aimed to assess the morphological diversity and model habitat suitability using the Maximum Entropy (MaxEnt) approach for O. tigillarium in the coastal areas of Riau Province. Morphological samples were collected from various coastal habitats and analyzed using Principal Component Analysis (PCA). Habitat suitability modeling was conducted based on 72 occurrence points and relevant environmental variables. The results revealed low qualitative morphological diversity, with notable differences in stem color, spine shape, and rachillae color during flowering and fruiting. PCA revealed three clusters based on quantitative variation, with PC1 and PC2 explaining 54.8% of total morphological variation. The MaxEnt model performed exceptionally well, with an Area Under Curve value of 0.993. Highly suitable habitats (IHS 0.6-1.0) were primarily located in Bengkalis. This area is highly suitable for the long-term conservation of O. tigillarium.